Rancang Bangun Aplikasi Bimbingan Skripsi Online Mahasiswa Berbasis Mobile (Studi Kasus Program Studi Informatika Universitas Kristen Petra) - Semuel Lesbassa; Alexander Setiawan; Lily Puspa Dewi (Jurnal Infra, 2021)
During the guidance process, students must bring a guidance form to record the results of their guidance with the supervisor. But students often do not bring the guidance form so that guidance activities are hampered. And in online learning right now because of the Corona Virus Disease 19 (Covid-19) pandemic. There are difficulties in contacting the lecturer to be used as a supervisor so that it can hinder students in doing their final assignment. Seeing the background of this problem, an online thesis guidance application was designed with a mobile application in which there is a guidance form that can be accessed by students and supervisors anytime and anywhere. And has features that can help students communicate with lecturers in conducting their guidance. The results obtained from this application include a thesis submission form, a guidance form for the guidance process and a chat feature for student and lecturer communication